Effect of rutin on the structural and functional properties of ovalbumin - Qian Cui; Yanqiu Ma; Xue Mao; Guozhi Zhao; Siyi Huang; Xingyu Wen; Zimeng Zhu; Xin Gao (Poultry Science, 2025)
Phenolic substances affect protein functionality. This study aimed to examine how rutin influences the gel properties, antioxidant activity, and structure of ovalbumin (OVA). Increasing rutin concentration enhanced the gel hardness of OVA but reduced soluble protein content with no significant effect on water retention. At 0.25 % rutin concentration, the gel hardness of OVA increased from 109.33 g to 292.60 g, while soluble protein content decreased from 1.08 mg/mL to 0.97 mg/mL. Rutin modification significantly increased the storage and loss moduli of OVA gel, making its structure more compact. At 0.25 % rutin, antioxidant analysis showed increases in the DPPH radical scavenging rate (127 %), ABTS radical scavenging rate (112 %), hydroxyl radical scavenging rate (4167 %), and reducing power (101 %) of OVA. Fluorescence spectroscopy, surface hydrophobicity, free sulfhydryl content, and circular dichroism spectra revealed that higher rutin concentrations reduced fluorescence intensity and surface hydrophobicity while increasing the free sulfhydryl content of OVA. The α-helix content of OVA decreased, while β-sheet content increased. In addition, it was confirmed that OVA and rutin were bound by hydrophobic interaction. The quenching mechanism was static quenching. Rutin alters the structure and functional properties of OVA, providing a theoretical foundation for developing antioxidant and high-gel OVA variants.